Problematika Hukum Implementasi Sifat Final dan Binding Putusan yang Dibuat oleh BASYARNAS dalam Penyelesaian Sengketa Bisnis Syariah - Khasanah, Karimatul (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2018)
BASYARNAS’s verdict in resolving dispute can be negotiated or cancelled by submitting nullification to the Religious Court if the parties or one of them felt dissatisfied with the BASYARNAS verdicts. This case is important to be reviewed academically because of its paradox and ambiguity. On the one hand the decision is final and binding, but on the other hand it could be cancelled through the Religious Court. If the BASYARNAS verdicts really want to be final and binding, the nullification of the verdicts should be abolished. It can be replaced by an amendment of the verdict submitted to BASYARNAS and handed back to the arbitrator (arbitrator panel) who handles the dispute. Apart being fast and confidential, the arbitrator (judge) is more aware of the case, the reasons, evidences and witnesses of the dispute.